Productive qualities of young quails with the use of fennel oil (Foeniculum vulgare) in compound feed - T. Kholiavska; D. Umanets (Тваринництво та технології харчових продуктів, 2024)
Due to the emergence of antibiotic resistance of microorganisms, it is important to study the effectiveness of phytobiotics in poultry feeding. The aim of the study was to identify the ideal dosage of fennel oil (Foeniculum vulgare) for feeding meat quail. To conduct the study, 4 groups of quails of day-old age were formed, 100 birds each. The first group consumed basic compound feed and was therefore a control group. In the mixed feed of experimental group 2, 0.1% of vegetable oil was replaced with fennel oil, in experimental groups 3 and 4 – 0.2% and 0.3%, respectively. The average daily gains during the growing period were the largest in experimental group 4 – 0.46 g or 7.07% more than the control group. The advantage over the control of quails in experimental group 3 was 0.43 g or 6.61%, and in experimental group 2 – 0.34 g or 5.22%. Throughout the experiment, birds in the experimental groups consumed 2.41-4.49% more feed compared to the control group. However, the feed cost per kilogram of body weight gain was 5.04- 6.97% lower than in the control group. Quails in experimental group 2 showed an advantage over the control group, with breast muscle weight higher by 2.5 g (5.22%) and leg muscle weight by 1.1 g (3.74%). The birds of experimental group 3 were ahead of the control in terms of breast muscle weight by 3.5 g or 7.31%, and leg muscles – by 1.5 g or 5.10%. Quails in experimental group 4 surpassed the control group, showing a 3.9 g (8.14%) increase in breast muscle weight and a 1.9 g (6.46%) increase in leg muscle weight. Thus, the introduction of fennel oil in a dose of 0.1- 0.3% into the composition of quail compound feed allows improving growth and achieving better productivity indicators